Diel vertical movements and feeding behaviour of blue humphead parrotfish Scarus ovifrons in a temperate reef of Japan. Issue 1 (7th March 2021) - Gomi, Kazuma; Nakamura, Yohei; Kanda, Masaru; Honda, Kentaro; Nakaoka, Masahiro; Honma, Chiho; Adachi, Masao
Abstract: The feeding ecology of scarinine parrotfishes on tropical coral reefs has received considerable attention in the past few decades; nonetheless, relatively few studies have been conducted in high‐latitude reefs. Among the Indo‐Pacific Scarus species, Scarus ovifrons is unique, being largely restricted to the warm temperate waters of Japan. Nonetheless, there is very little information available on the feeding ecology of this species. In this study, the authors used acoustic telemetry to detect the diel vertical movement patterns of S. ovifrons, video survey to detect its feeding depths and substrata and focal follow survey and genetic analysis to identify algae composition on the feeding scars at Kashiwajima Island, southwestern Japan (32° 46′ N, 132° 38′ E). Acoustic telemetry revealed that S. ovifrons spent most of its time in shallow water (<10 m) during the day and slept in deeper water (10–15 m) at night. Video and focal follow surveys revealed that most fishes of various sizes regularly took bites on epilithic algae and detrital materials on rocky substrata at depths of <10 m, but large fishes (>40 cm total length) sometimes took bites directly on live corals ( Acropora solitaryensis ) at the 5 m depth zone where live tabular corals dominated the benthos. Molecular phylogenetic analyses revealed that epilithic algae collected from feeding scars were mainly composed of Rhodophyta, and coralline algae were less often targeted. Overall, this study revealed that S. ovifrons feeds mostly at depths <10 m, and the feeding algae substrata of the species are similar to those of tropical coral reef parrotfishes.